LEARNING INTERESTS OF CLASS X STUDENTS IN ENGLISH SUBJECTS IN ONE OF SENIOR HIGH SCHOOLS IN BANDUNG - Lilis Siti Aisyah; Anita Anggraeni; Agung Putri Pratama (IKIP Siliwangi, 2022)
This research is a preliminary study that aims to determine the interest of students in one of SMA in Bandung in learning English. This research uses mix methods (qualitative and quantitative ) based on questionnaire results. The results showed that 32.6% liked English lessons. When English lessons took place the